A review on the enhancement of circular economy aspects focusing on nanocellulose composites - Azka, Muhammad Adlan; Adam, Adib; Ridzuan, S.M.; Sapuan, S.M.; Habib, Abdul (Elsevier, 2024)
Researchers are now focusing on using the circular economy model to manufacture nanocellulose composites due to growing environmental issues related to waste management. The circular economy model offers a sustainable solution to the problem by optimizing resource efficiency and waste management by reducing waste, maintaining value over time, minimizing the use of primary resources, and creating closed loops for goods, components, and materials. With the use of the circular economy model, waste, such as industrial, agricultural, and textile waste, is used again to produce new products, which can solve waste management issues and improve resource efficiency. In order to encourage the use of circular economy ideas with a specific focus on nanocellulose composites, this review examines the concept of using circular economy, and explores ways to make nanocellulose composites from different types of waste, such as industrial, agricultural, and textile waste. Furthermore, this review investigates the application of nanocellulose composites across multiple industries. In addition, this review provides researchers useful insights of how circular economics can be applied to the development of nanocellulose composites, which have the goal of creating a flexible and environmentally friendly material that can address waste management issues and optimize resource efficiency.